STUDI LITERATUR PENGARUH EKSPOR, IMPOR, NILAI TUKAR RUPIAH, DAN TINGKAT INFLASI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Ani Syafa'ah (Econetica: Jurnal Sosial, Ekonomi, dan Bisnis, 2025)
This research has important implications for economic policy making in Indonesia. Appropriate policies in managing exports, imports, the rupiah exchange rate, and the inflation rate can accelerate economic growth, create jobs, and improve the welfare of society as a whole. The purpose of this study is to identify how much influence these variables have on Indonesia's economic growth and how the interactions between these variables. The method used in this research is a literature review study by reviewing several research articles that have been published and are related to the same research problem and research results obtained through the database in the Google Scholar publication. Based on 8 literature studies, the journals that have been analyzed have similarities that with exports, imports, exchange rates and inflation will have a good effect and have a significant influence on economic growthIndonesia. This is because exports make the largest contribution to GDP in Indonesia. The higher the real exchangerate, the more it will encourage exports and others and be able to influence Indonesia's economic growth.